PROBLEM SOLVING DESIGN BASED ARABIC LANGUAGE LEARNING APPROACH IN LANGUAGE SKILLS - Khairanis, Retisfa; Aldi, Muhammad (As-Sulthan Journal of Education, 2025)
This research aims to explore the effectiveness of a problem-solving design-based Arabic language learning approach in improving students' language skills. The scope of the research covered intermediate level students in a junior high school in Indonesia. The method used was a qualitative approach with a classroom action research design, which involved observation, interviews and document analysis to collect data. The results show that the application of this approach can significantly improve students' learning motivation and Arabic language skills. Students showed improvement in speaking, listening, reading and writing skills through activities designed to solve real problems. In addition, the interaction between students during the learning process also strengthens their understanding of the Arabic language. The conclusion of this research confirms that the problem-solving design-based learning approach is not only effective in improving Arabic language skills, but also encourages students to think critically and creatively. Therefore, this approach is recommended to be applied more widely in Arabic language teaching at various levels of education.